Os desafios para a democratização do acesso a água no semiárido da caatinga do sertão central cearense - Valdivia, Antonia Marcia Araujo Guerra Urquizo (2012)
This dissertation presents in itself important components of critical analysis about the challenge of democratization of the access to potable (drinkable) water at the seminar of the central wild drought and arid region of caatinga, in the state of Ceará, when defending with grate enthusiasm that the fact of northeastern drought (lack of water) is not a simple environmental phenomenon but it is, in truth, one of the most complete expressions (utterances) of the social question. To this, the social Marxist theory, takes as base the structure of development of this research the way that put the conflicts for water as part of the capitalist system. It is based on the exploration and domination, either, from the employees and of the natural richness. The theorethical methodological argumentation about the present study is supported by various pillars indispensable for the construction of this dissertation developed (divided) into four chapters: 1) POLITICAL CONJUNTURE OF THE WATER It deals with the historic and distribution of water on the earth (ground), and also, the political management of the water, starting from the commitees of hydrographical basins, the world forum of the water and of the counsels of hydric resources, beside of problemize the current role of the world council of water in the commercialization of the water. 2) THE WATER AS MARCHANDISE (COMODITY) IN THE CAPITALIST SYSTEM It discusses aspects of the capitalist system in the expropriation of the water to transform it into merchandise and yet exposes the capitalist democracy of the water, mainly the offensive of the neo-liberal project in Latin America. The war for water and for the life . 3) THE BRAZILIAN NORTHEAST INVENTION It brings elements to analyse the socio-historical formation of the brazilian space in special the north-eastern Region, resultant of a national pact in intrinsical resistence-domination relation, country-city, and development-subdevelopment.; time space. It discusses yet the agreements and divergencies, respecting the North-eastern drought (seca) a critical vision about the heterogeneous condition of DNOCS. 4) THE WAY OF LOOKING FOR WATER It shows the ethics as the structural part of the socio-historical dynamics emerged from the dispute to power, configured by the conflicting interests of the social classes, besides socialize antihegemonical, iniciatives, having as perspective the democratization of the water. Jet this reseach is regarded, of importance, not, only for the municipality of Itatira/CE (birth-place of the author) but, when taking in account the national hydrographical scenary making part of the discussions inherent to the social-service contribution, in the effort for the democratization of the access to water